Implementation of Good Governance in the Appointment of Regional Acting Heads - Maziyah, Dania Shofi; Kusumo, Haryo Hendro; Mabrury, Aditya Prima; Normasari, Riski Dyah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The study examines how well good governance practices are followed when choosing temporary regional leaders (acting regional heads). These appointments are sometimes influenced by powerful politicians and don't involve the public enough. The research uses existing documents (like legal codes and scholarly articles) to explore this issue. The findings suggest the current system for picking acting regional heads lacks transparency, public involvement, and accountability. To make the process fairer and more open, improvements are needed in following good governance principles. The study is based on Indonesian law (Law No. 30 of 2014) and government regulations (Minister of Home Affairs Regulation No. 4 of 2023).